2022
DOI: 10.1515/iral-2021-0223
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic prediction in L2 learners: evidence from English disjunction processing

Abstract: This study examined the extent to which second language (L2) learners’ syntactic prediction resembles or differs from native speakers’ and the role of L2 proficiency in this process. An experimental group of 135 Chinese learners of English and a control group of 58 English native speakers participated in a phrase-by-phrase self-paced reading task where the experimental sentences were contrastive in whether the DP disjunction was preceded by either or not. To ensure that the participants had sufficient knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…This treatment was to remove completely unusable data and differed from the trimming procedure that seeks to rid the data sets of outliers. Although Fang and Wu (2022b) logarithmically transformed and residualized the RTs on the length of the region before their further analysis, we used the "raw" RTs in our analysis for consistency across the three data sets. As a sensitivity analysis, we confirmed that using the logged, residualized RTs did not change our conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This treatment was to remove completely unusable data and differed from the trimming procedure that seeks to rid the data sets of outliers. Although Fang and Wu (2022b) logarithmically transformed and residualized the RTs on the length of the region before their further analysis, we used the "raw" RTs in our analysis for consistency across the three data sets. As a sensitivity analysis, we confirmed that using the logged, residualized RTs did not change our conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, faster reading times can be expected when learners read a sentence containing formulaic language than a matched control version. For example, Fang and Wu (2022b) investigated Chinese learners' knowledge of the either-or construction in English. In an SPR task, participants read stimulus sentences such as Jay painted either | the big house | or the old car | for his family over the summer (p. 9), with or without either.…”
Section: Use Of Response-time Difference Measuresmentioning
confidence: 99%
See 3 more Smart Citations